Morphological characterization of indigenous potato (Solanum tuberosum) genotypes - CHAUDHARY, BABITA; DALAMU; GUPTA, V K; LUTHRA, S K; KUMAR, M (The Indian Journal of Agricultural Sciences, 2024)
Potato (Solanum tuberosum L.) is the most important non-grained food and vegetable crop lauded for its nutritional and health benefits. Identifying any new potato genotype primarily depends on its morphological traits, including vegetative, floral and tuber parameters. The present study was carried out during 2020–21 and 2021–22 at the research farm of ICAR-Central Potato Research Institute, regional station, Modipuram, Uttar Pradesh and at ICAR-Central Potato Research Institute, Kufri-Fagu unit, Himachal Pradesh (for floral traits) to evaluate the potato genotypes for vegetative and tuber traits. The experiment was laid out in a randomized complete block design (RCBD) with three replications. Total of 64 indigenous potato genotypes were characterized for 51 morphological traits for distinctiveness, uniformity and stability (DUS) test guidelines. For all traits, there was a high degree of variability between genotypes. Early maturing varieties are preferred owing to their suitability to fit into the potato-wheat (Triticum aestivum L.)- paddy (Oryza sativa L.) cropping system. Most genotypes were either early or medium maturing based on foliage senescence. High variability was observed for tuber shape, i.e. genotypes bearing flattened, round, ovoid, oblong, long-oblong and reniform-shaped tubers were available. Tuber skin and flesh colour determining consumer preference depicted variability from whitish cream to dark purple-black skinned tubers. Novel genotypes bearing variegated tuber flesh with a niche market of specific consumer segments were noticed in genotypes Red flesh, Bareilly red, DRR Blue, Badami aloo and Kala aloo. Moreover, the results obtained from the present investigation indicated that the description of 64 indigenous potato genotypes based on notes can be used as a reference for the protection of new varieties under the Protection of Plant Varieties and Farmers Right Act (PPV&FRA) rules as well as a comparison against new candidate varieties.